Fit and Viable Determinants of Gamification in Christian Religious Studies in Developing Economy Context - Akuetteh, Alfred Patterson (Journal of religion, media and digital culture, 2023)
Gamification has been utilized in bible applications for religious learning activities to create excitement and encourage positive behavioral outcomes. However, there is a noticeable gap in the effectiveness and viability of gamified bible applications, particularly among Ghanaian Christian faiths. In this study, we explored the fit and viability of gamification in Christian religious studies. Based on the Fit-Viability Theory, we analyzed data from 432 respondents from various Christian denominations in Ghana using structural equation modelling. Our findings revealed that Task and Technology Characteristics, Economic, Organizational, and individual Christian Doctrines significantly influence the adoption and use of gamified Bible applications in a developing country context.